2013
DOI: 10.1021/am401627u
|View full text |Cite
|
Sign up to set email alerts
|

Designed Fabrication of Unique Eccentric Mesoporous Silica Nanocluster-Based Core–Shell Nanostructures for pH-Responsive Drug Delivery

Abstract: A novel and facile strategy using poly(acrylic acid) (PAA) as a nanoreactor and template has been proposed and applied for the first time to fabricate a novel and unique class of multifunctional eccentric Fe3O4@PAA/SiO2 core-shell nanoclusters (NCs) consisting of a single Fe3O4 nanoparticle (NP), PAA, and eccentric SiO2 NCs that are composed of a large number of small fluorescent SiO2 NPs. Interestingly, the resulting eccentric PAA shell around Fe3O4 NPs as a high water-absorbent polymer is like a "reservoir" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 65 publications
0
53
0
Order By: Relevance
“…Under mildly acidic conditions, the H + competes with the hydrogen-bond-forming groups and weakens the hydrogen-bonding interactions35. Moreover, at low pH, DOX becomes more hydrophilic and water soluble; thus, more DOX is released from the tHBcAg-PAA-DOX nanoparticles into solution283436. Because the microenvironment around tumour tissues, and in intracellular lysosomes and endosomes are slightly acidic192836, DOX is released after being taken up by tumour tissues (pH 5–5.5).…”
Section: Discussionmentioning
confidence: 99%
“…Under mildly acidic conditions, the H + competes with the hydrogen-bond-forming groups and weakens the hydrogen-bonding interactions35. Moreover, at low pH, DOX becomes more hydrophilic and water soluble; thus, more DOX is released from the tHBcAg-PAA-DOX nanoparticles into solution283436. Because the microenvironment around tumour tissues, and in intracellular lysosomes and endosomes are slightly acidic192836, DOX is released after being taken up by tumour tissues (pH 5–5.5).…”
Section: Discussionmentioning
confidence: 99%
“…At room temperature, the DOX-loaded Cu 39 S 28 -FA remained loaded at pH 7.4, and only less than 10 % DOX was released in 24 h. In pH 5.0 buffer, DOX was quickly released to 32 % of the original amount in the first 8 h, and ~45% in 24 h. This pH responsive controlled-release property can be attributed to the dissociation of electrostatic interaction between the positively-charged DOX molecules and negatively-charged Cu 39 S 28 -FA HNPs, due to the weak electrostatic interaction of DOX with COO − and the enhanced solubility of DOX under lower pH environment. 4042 The Cu 39 S 28 -FA HNPs can effectively leak DOX during the blood circulation and increase the delivery efficacy in cancer cells. Moreover, the release profiles at 37 °C was also tested (Figure S5), which was a reflection of actual physiological environment.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [95] fabricated multifunctional Fe 3 O 4 @poly(acrylic acid)/SiO 2 core/shell nanostructures that consisted of a single Fe 3 O 4 nanoparticle, poly(acrylic acid), and SiO 2 , and the as-prepared core-shell nanostructures had multiple functions of fluorescence imaging, high drug loading capacity, and pH-responsive drug release. Li et al [96] reported a multifunctional fluorescent-magnetic (concentricFe 3 O 4 @SiO 2 )@polyacrylic acid core-double shell nanocomposite with ultrahigh drug storage capacity for cell imaging and pHresponsive drug delivery.…”
Section: Inorganic/organic-composite Ph-responsive Drug-delivery Systemsmentioning
confidence: 99%